Eosinophil is a predictor of severe immune-related adverse events induced by ipilimumab plus nivolumab therapy in patients with renal cell carcinoma: a retrospective multicenter cohort study - Tasaki, Yoshihiko; Hamamoto, Shuzo; Yamashita, Shimpei; Furukawa, Junya; Fujita, Kazutoshi; Tomida, Ryotaro; Miyake, Makito; Ito, Noriyuki; Iwamoto, Hideto; Mimura, Yoshihisa; Sugiyama, Yosuke; Unno, Rei; et al. (Frontiers in Immunology, 2025)
IntroductionImmune-related adverse events (irAEs) induced by immune checkpoint inhibitors are difficult to predict and can lead to severe events. Although it is important to develop strategies for the early detection of severe irAEs, there is a lack of evidence on irAEs associated with ipilimumab plus nivolumab therapy for metastatic renal cell carcinoma (RCC). Therefore, this study aimed to investigate the association between eosinophil and severe irAEs in patients receiving ipilimumab plus nivolumab therapy for RCC.MethodsIn this retrospective study, 161 patients receiving ipilimumab plus nivolumab therapy for RCC were divided into three groups based on whether they experienced <grade 2 irAEs (non-severe irAE group), ≥grade 3 irAEs (severe irAE group), or not (non-irAE group). We examined the proportion of eosinophils before and 2 weeks after treatment (baseline and 2-week samples, respectively).ResultsAlthough the eosinophil in the baseline samples did not differ between the severe irAE and non-irAE groups (2.8% vs. 2.5%, P = 0.75), regarding the 2-week samples, the eosinophil was significantly higher in the severe irAE group (mean, 6.6% vs. 3.3%; P < 0.05). Multivariate analysis showed that an eosinophil of ≥3.0% was a risk factor for severe irAEs (odds ratio, 6.01). Median progression-free survival (mPFS), mPFS from the start of ipilimumab plus nivolumab therapy to second-line therapy (mPFS2), and median overall survival (mOS) were the shortest in the non-irAE group. Although the mPFS did not differ between the severe and non-severe irAE groups (9.2 vs 14.2 months, P = 0.45), notably, mPFS2 and mOS in the former group tended to be shorter than those in the latter group (mPFS2: 29.2 vs not reached, P = 0.10; mOS: 36.9 vs 52.3 months, P = 0.06).DiscussionAn increased eosinophil 2 weeks after ipilimumab plus nivolumab therapy may be a predictor of severe irAEs, which are associated with poor prognoses, compared with non-severe irAEs among patients with RCC. We provide a novel rationale for the importance of monitoring eosinophil counts for the early detection of severe irAEs.